2021
DOI: 10.1080/10872981.2021.1929798
|View full text |Cite
|
Sign up to set email alerts
|

The strength of our stories: a qualitative analysis of a multi-institutional GME storytelling event

Abstract: Context: Storytelling is a powerful tool for encouraging reflection and connection among both speakers and listeners. While growing in popularity, studying the benefits of formal oral storytelling events within graduate medical education remains rare. Our research question was: could an oral storytelling event for GME trainees and faculty be an effective approach for promoting well-being and resilience among participants? Methods: We used multiple approaches to gather perspectives from physician participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Such attitudes can be replaced with a culture of authenticity and vulnerability during the medical school and residency training process as well as deliberate approaches to reduce IP among physicians in practice. 11,32,53 Tactics to advance these aims might include COM-PASS (Colleagues Meeting to Promote and Sustain Satisfaction) groups, 54,55 storytelling events, 56,57 sharing of personal narratives, 12,[58][59][60] and small group discussions. 30,61 Senior physicians discussing challenging times in their career and sharing their "failure resume" during department meetings or other forums can also be a useful approach to illustrate to junior physicians that many of their role models have also faced challenges throughout their career.…”
Section: Resultsmentioning
confidence: 99%
“…Such attitudes can be replaced with a culture of authenticity and vulnerability during the medical school and residency training process as well as deliberate approaches to reduce IP among physicians in practice. 11,32,53 Tactics to advance these aims might include COM-PASS (Colleagues Meeting to Promote and Sustain Satisfaction) groups, 54,55 storytelling events, 56,57 sharing of personal narratives, 12,[58][59][60] and small group discussions. 30,61 Senior physicians discussing challenging times in their career and sharing their "failure resume" during department meetings or other forums can also be a useful approach to illustrate to junior physicians that many of their role models have also faced challenges throughout their career.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown oral story telling, the sharing of how a person copes in times of struggle, increases empathy and decreases burnout in healthcare settings. 55 , 58 Future research should seek to determine whether simulated learning experiences can mitigate the development of personal distress in early career professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Such storytelling would be an opportunity to increase connection with peers and conquer fears and worries through volubility moments. 4…”
Section: To the Editormentioning
confidence: 99%